Perception et stratégies d’adaptation aux incertitudes climatiques par les exploitants agricoles des zones marécageuses au Sud-Kivu - Arsène Mushagalusa Balasha; Jean-Hélène Kitsali Katungo; Benjamin Murhula Balasha; Lebon Hwali Masheka; Aloïse Bitagirwa Ndele; Volonté Cirhuza; Jean -Baptiste Assumani Buhendwa; Innocent Akilimali; Nicanor Cubaka; Benoît Bismwa (VertigO)
Smallholder farming vulnerability to climate change results from its direct dependence on climatic factors (rainfalls, temperatures, solar radiation). In the DR Congo, where 3/4 of the population depends on this type of agriculture, the combined effects of climate change and COVID-19 have been added to existing structural issues (example : persistent insecurity, impassable agricultural feeder roads ) to exacerbate threats to livelihoods of rural and periurban communities. Farmers ‘interviews within swamps of South Kivu reveal that the disruption of climatic elements such as rainfall and temperature patterns upsets farmers' endogenous knowledge of the climate. These farmers experience heavy and short rainfall (76 %), rising temperatures and a dry season likely long. Results from the binary logistic regression show that the appearance of new pests and the irregularity in rainfall patterns increase significantly farmers' conviction of climate change in the study area. Perceived impacts of climate change that farmers fear include the decline of soil fertility, decreasing yields, crops failure due to floods. Farmers’ adaptation strategies include the cleaning up streams, mulching as well as the application of manure, crop diversification and use of chemical pesticides that is currently farmers ‘preferred option to control pests. This paper provides valuable information that can guide policy makers as well as those involved in agricultural development to define a program that aims at strengthening farmers ’capacity to adapt to climate change by formulating new strategies based on existing local knowledge.